PROSES PENYIDIKAN TINDAK PIDANA YANG DILAKUKAN OLEH ANAK - Cahyono, Rudi; Muhamad Dluha; Samsul Huda (JUSTNESS - Jurnal Hukun dan Agama, 2023)
Abstract Children who incidentally have not been able to think and act maturely sometimes do things that are irregular and against the law that can result in harm to others so that the victims and perpetrators admit to being unfair to each other. crimes committed by children. The benefits of this research are to find out the efforts or processes of investigation and investigation of criminal acts carried out by children, the method taken using the Juridical Empirical method by combining primary and secondary data obtained from the field in the form of interviews and other legal sources. The research in writing this thesis is the mechanism of investigation and investigation carried out by the Probolinggo resort police in criminal acts committed by children is to use the legal basis of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The juvenile criminal justice system is in accordance with Law Number 11 of 2012. The suggestion of this research is that legal protection in the process of investigating children should be given more attention because this concerns the future of children who still need guidance from adults. Keywords: Investigation, Crime, Children